Analysis of electronic parameters and interface states of boron dispersed triethanolamine/p-Si structure by AFM, I-V, C-V-f and G/?-V-f techniques - Yakuphanoğlu, Fahrettin; Okur, Salih (Elsevier Science Bv, 2010)
The electronic parameters and interface state properties of boron dispersed triethanolamine/p-Si structure have been investigated by atomic force microscopy, I-V, C-V-f and G/omega-V-f techniques. The surface topography and phase image of the TEA-B film deposited onto p-Si substrate were analyzed by atomic force microscopy. The atomic force microscopy results show a homogenous distribution of boron particles in triethanolamine film. The electronic parameters (barrier height, ideality factor and average series resistance) obtained from I-V characteristics of the diode are 0.81 eV, 2.07 and 5.04 k Omega, respectively. The interface state density of the diode was found to be 2.54 x 10(10) eV(-) cm(-2) under V(g) = 0. The obtained D(it) values obtained from C-V and G/omega measurements are in agreement with each other. The profile of series resistance dependent on voltage and frequency confirms the presence of interface states in boron dispersed triethanolamine/p-Si structure. It is evaluated that the boron dispersed triethanolamine controls the electronic parameters and interface properties of conventional Al/p-Si diode. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Metal/semiconductor contacts; Boron; Interfacial state density